The PL6-Family Plasmids of Haloquadratum Are Virus-Related - Dyall-Smith, Mike; Pfeiffer, Friedhelm (Frontiers in Microbiology, 2018)
Plasmids PL6A and PL6B are both carried by the C23T strain of the square archaeon Haloquadratum walsbyi, and are closely related (76% nucleotide identity), circular, about 6 kb in size, and display the same gene synteny. They are unrelated to other known plasmids and all of the predicted proteins are cryptic in function. Here we describe two additional PL6-related plasmids, pBAJ9-6 and pLT53-7, each carried by distinct isolates of Haloquadratum walsbyi that were recovered from hypersaline waters in Australia. A third PL6-like plasmid, pLTMV-6, was assembled from metavirome data from Lake Tyrell, a salt-lake in Victoria, Australia. Comparison of all five plasmids revealed a distinct plasmid family with strong conservation of gene content and synteny, an average size of 6.2 kb (range 5.8-7.0 kb) and pairwise similarities between 61-79%. One protein (F3) was closely similar to a protein carried by betapleolipoviruses while another (R6) was similar to a predicted AAA-ATPase of His 1 halovirus (His1V_gp16). Plasmid pLT53-7 carried a gene for a FkbM family methyltransferase that was not present in any of the other plasmids. Comparative analysis of all PL6-like plasmids provided better resolution of conserved sequences and coding regions, confirmed the strong link to haloviruses, and showed that their sequences are highly conserved among examples from Haloquadratum isolates and metagenomic data that collectively cover geographically distant locations, indicating that these genetic elements are widespread.